Trace element geochemistry of sphalerite in contrasting hydrothermal fluid systems of the Freiberg district, Germany: insights from LA-ICP-MS analysis, near-infrared light microthermometry of sphalerite-hosted fluid inclusions, and sulfur isotope geochemistry - Bauer, Matthias E.; Burisch, Mathias; Ostendorf, Jörg; Krause, Joachim; Frenzel, Max; Seifert, Thomas; Gutzmer, Jens (Mineralium deposita, 2019)
The historic silver mining district of Freiberg (Germany) comprises hydrothermal vein-style mineralization of Permian and Cretaceous age. We compare sphalerite compositions with associated ore-forming fluids and constrain the behavior of critical metals such as In, Ge, and Ga in contrasting hydrothermal environments. Fluid inclusion studies reveal that the Permian veins formed due to boiling and cooling of a low-salinity (0 to 6% eq. w [NaCl]) magmatic-hydrothermal fluid at 350 to 230 °C. In contrast, Cretaceous veins formed by mixing of highly saline (17 to 24% eq. w [NaCl + CaCl 2 ] and variable Na/(Na + Ca) ratios) brines at low temperatures (~ 120 °C). Sulfides of the Permian ore stage have a narrow range of δ 34 S VCDT from − 2.3 to + 0.9‰, while the sulfides of the Cretaceous stage have a large scatter and significantly more negative δ 34 S VCDT values (− 30.9 to − 5.5‰), supporting the different nature of the hydrothermal systems. Contrasting fluid systems and ore-forming mechanisms correspond to markedly different trace element systematics in sphalerite. Permian sphalerite is significantly enriched in In (up to 2500 μg/g In) relative to two sphalerite generations of Cretaceous veins. The latter have higher Ge (up to 2700 μg/g Ge) and Ga (up to 1000 μg/g Ga) concentrations. The observed trace element systematics of different sphalerite generations imply that In is enriched in high-temperature, low- to intermediate-salinity fluids with a significant magmatic-hydrothermal fluid component, while Ge and Ga are more concentrated in low-temperature, high-salinity crustal fluids with no obvious magmatic-hydrothermal affiliation.